2023
DOI: 10.3389/fpsyg.2023.1216437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Jigsaw method on student educational outcomes: systematic review and meta-analyses

Abstract: IntroductionCooperative learning methods are particularly interesting for building more inclusive schools; however, they have not been widely implemented. Among cooperative learning methods, the Jigsaw strategy is attractive for teachers, as it seems to be easy to implement and follow its four-step teaching structure; in addition, this method is believed to improve students' socialization and learning. To identify the effects of the Jigsaw method accurately, a systematic review of studies that have tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…International educational standards prioritize inclusive schools (Hesjedal et al, 2015), and cooperative learning approaches (Vakilifard et al, 2020) are shown to be helpful in promoting inclusion. Cooperative learning, where people engage and learn together, is a promising educational technique (Cochon Drouet et al, 2023). It allows students to collaborate and use their friends as a valuable learning resource.…”
Section: Introductionmentioning
confidence: 99%
“…International educational standards prioritize inclusive schools (Hesjedal et al, 2015), and cooperative learning approaches (Vakilifard et al, 2020) are shown to be helpful in promoting inclusion. Cooperative learning, where people engage and learn together, is a promising educational technique (Cochon Drouet et al, 2023). It allows students to collaborate and use their friends as a valuable learning resource.…”
Section: Introductionmentioning
confidence: 99%